Microsoft® Windows® XP Inside Out, 2nd Edition - Bott, Ed; Siechert, Carl; Stinson, Craig (Microsoft Press, 2004)
Take your Windows XP knowledge to the next level! Designed for advanced home and office users, this thoroughly updated second edition delivers in-depth information on core and advanced Windows XP topics, including all-new coverage of Windows XP Service Pack 2, Microsoft Windows Server 2003, Microsoft Windows XP Media Center Edition, Windows Media Series 9, and Windows Movie Maker 2. The award-winning Inside Out format makes it easy to find the timesaving solutions, troubleshooting tips, and workarounds you needand it features new Reality Check sidebars, which offer the straight scoop on popular wisdom about Windows XP.